ANALISIS FINANSIAL PEMANFAATAN AMPAS TEBU (BAGASSE) SEBAGAI BAHAN BAKAR PEMBANGKIT LISTRIK DI PT GUNUNG MADU PLANTATIONS - Silva Anggun Larasati; Zainal Abidin; Teguh Endaryanto (Lampung University, 2019)
This research aimed to analyse the financially of feasibility and break even point of power plant. This is a case study at PT Gunung Madu Plantations, Lampung. Data collection was conducted in May 2017 and was analyzed by financially analysis and break even point analysis. The investment of power plant at PT Gunung Madu Plantations financially wass feasible, with NPV value of Rp1,437,425,146,844; Net B/C of 7.00; Gross B/C of 1.81, IRR of 34.84 percent, and payback periode of 1.75. Amount of revenue and electricity produced by PT Gunung Madu Plantations has reached break even point. The result of this analysis showed that the average of BEP revenue was Rp32,548,133,618 and BEP electricity production was 49,994,808 KWh.Key words: bagasse, break even point, financially